2018 13th Annual Conference on System of Systems Engineering (SoSE) 2018
DOI: 10.1109/sysose.2018.8428723
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of evidential occupancy grids for cooperative perception

Abstract: In the field of autonomous navigation, perception of the driving scene is one of the essential elements. Existing solutions combine on-board exteroceptive sensors, and are capable of understanding some of the near vehicle's dynamic surrounding environment. Furthermore, the perception capability of each vehicle can be enhanced by wireless information sharing if vehicles in the neighborhood transmit pertinent information. The primary benefit of such approach is to enable and improve the performance-safety of coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Sensors can identify and track targets, but the reality will be blocked by other vehicles and infrastructure, resulting in perception information reduction. Camarda et al [94] used the fusion framework of lidar and wireless communication technology to realize the urban scene representation. The uncertainties of vehicle attitude and the measured data of switched sensors are used to improve the vehicle perception.…”
Section: Research On Traffic Conflict Based On Intelligent Vehiclmentioning
confidence: 99%
“…Sensors can identify and track targets, but the reality will be blocked by other vehicles and infrastructure, resulting in perception information reduction. Camarda et al [94] used the fusion framework of lidar and wireless communication technology to realize the urban scene representation. The uncertainties of vehicle attitude and the measured data of switched sensors are used to improve the vehicle perception.…”
Section: Research On Traffic Conflict Based On Intelligent Vehiclmentioning
confidence: 99%
“…In the latter, the back-projected images on the ground are merged by using the union method. However, our merging method is based on Dempster Shaffer Theory [21], [22] as presented in [9]. We have also used the average occupancy fusion method based on the intersection between detections to assess the efficiency of each fusion method in our vision-based cooperative context.…”
Section: A Related Workmentioning
confidence: 99%
“…2) Evidential merging method: We can also use the Dempster-Shafer Theory (DST) [21] to merge the LOGs as attempted in [9]. We give two possible statuses forming the universe given by the equation (7).…”
Section: Local Occupancy Grids Mergingmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, more information is shared compared to object-level fusion requiring a higher data rate. In [14], occupancy maps of different vehicles are superimposed using Dempster-Shafer reasoning to yield a fused map. It has been further shown that erroneous estimations of vehicle states pose a major challenge in map alignment [15], [16].…”
Section: A Related Workmentioning
confidence: 99%